PEMBUATAN ASIMETRIK MEMBRAN UNTUK PENGOLAHAN AIR : PENGARUH WAKTU PENGUAPAN TERHADAP KINERJA MEMBRAN - Ardian Dwi Yudhistira; Fajar Budi Iswanto; Tutuk D. Kusworo (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Membrane is the newest technology on water purification. Asymmetric membrane is one type of membrane that has a different pore size between surface (dense layer) and bottom layer. Surface layer has a very thin dense skin layer which use for filter, and bottom layer with a bigger pore size that use for support media. With such a structure, an asymmetric membrane can produce a higher flux than symmetric membrane. In membrane fabrication process, evaporation time becomes important because it can increase flux. Therefore, in this research will be assessed the effect of evaporation time as a variable. The purposes of this research are to make an asymmetric membrane using cellulose acetate polymers, to determine the effect of evaporation time toward morphology structure and membrane performance. Membrane was fabricated by phase inversion method with a variation of evaporation time 10, 15, and 25 second. Membrane composition consist of 23% CA, 5% PEG, and 1% tap water. Membrane was characterized by flux, rejection, and morphology analysis using SEM. Flux and rejection were measured using brackish water as a feed. The result of FTIR test, the membrane consist of the functional group -OH, C=O, CH3 - COOH, C-O-C ether and evaporation time of solvent make a different in absorption of diagnostic peek frequency. The result of SEM analysis, Asymmetric membrane was produced in this research. Membranes with optimum performance was obtained on the composition of  23% CA, 5% PEG, 1% tap water, and 25 second evaporation time with flux 4,465 L.Mˉ².h-1.bar-1, and percent rejection NTU 92%, percent rejection TDS 85%, and percent rejection Ca 81%,